From 1D to 3D: Fabrication of CH3NH3PbI3 Perovskite Solar Cell Thin Films from (Pyrrolidinium)PbI3 via Organic Cation Exchange Approach. Issue 6 (17th April 2020) - Miao, Yu; Fan, Haochen; Wang, Pengcheng; Zhang, Yue; Gao, Caiyan; Yang, Lian-Ming; Song, YanLin; Yang, Chunhe; Liu, Cai-Ming; Jiang, Ke-jian
Abstract : A new crystal form of 1D perovskite (pyrrolidinium)PbI3 (orthorhombic phase) is synthesized and characterized. The 1D perovskite has a good film formability by solution spin coating and is in situ transformed to 3D CH3 NH3 PbI3 via the organic cation exchange approach in CH3 NH2 atmosphere, which is dense and uniform. The converted 3D perovskite film is used as a light absorber, and the corresponding perovskite solar cell shows a power conversion efficiency of up to 19.2% under simulated 1 sun AM1.5G illumination (100 mW cm −2 ). Abstract : A new crystal form of 1D (pyrrolidinium)PbI3 perovskite is synthesized and transformed to the 3D CH3 NH3 PbI3 film via the cation exchange approach, and the corresponding perovskite solar cell shows a power conversion efficiency (PCE) of 19.2%.